Case Report: SMART ANTON: Anton-Babinski Syndrome in Stroke-Like Migraine Attacks (SMART) After Radiation Therapy: Two Rare Syndromes, One Case - Nicolas Nagysomkuti Mertse; Nicolas Nagysomkuti Mertse; Nicolas Nagysomkuti Mertse; René Müri (Frontiers in Neurology, 2022)
IntroductionWe describe the case of a 57-years-old patient who presented an Anton-Babinski syndrome in the context of a stroke-like migraine attack after radiation therapy (SMART).Case ReportThe patient was brought to the emergency room following a sudden loss of vision in the context of a pre-existing left-sided hemianopia after excision of a right occipital astrocytoma followed by radio-chemotherapy 35 years prior to his admission in our services. At admittance, he also presented hyperthermia, hypertension, and a GCS of 7. The MRI showed a leptomeningeal enhancement in the left temporal, parietal, and occipital lobes. After exclusion of other differential diagnoses, we diagnosed a cortical blindness in the context of a SMART syndrome affecting the left hemisphere. While the symptoms improved under corticosteroid therapy, the patient successively presented an Anton-Babinski syndrome, a Riddoch syndrome and a visual associative agnosia before finally regaining his usual sight.DiscussionThis is, to our knowledge, the first report of an Anton-Babinski syndrome in the context of a SMART syndrome. A dual etiology is mandatory for cortical blindness in SMART syndrome since the latter affects only one hemisphere. A SMART syndrome affecting the contralateral hemisphere in respect to the radiation site seems to be uncommon, which makes this case even more exceptional.